SPH Analysis of Sliding Material Volume and Influence Range of Soil Slope Under Earthquake - Zhang, Weijie; Yu, Ruihua; Chen, Yu; Chen, Shuxin (Frontiers in Physics, 2022)
The post-failure process of soil slope triggered by the earthquake is usually characterized by the large deformation, which can be properly addressed by the SPH simulation. Meanwhile, it is of engineering significance to evaluate the sliding volume and influence range after the failure of soil slope. The simulation method is based on the Drucker-Prager constitutive model and the SPH meth. The fixity boundary and free boundary particles are adopted to realize the applying of ground motion and the simulation of free field boundary, and this study proposes a dynamic analysis model for the whole-failure process simulation of soil slope under earthquakes. By comparing the PGA amplification coefficients obtained from model test and numerical simulation, the accuracy of ground motion input and ground motion response simulation is verified. Then, the proposed dynamic analysis method is used to simulate a shaking table test of soil slope in the literature. The results of the deformation of the soil slope after the test are compared to verify the accuracy of the analysis method in the soil slope displacement and the influence range under the earthquake action. Finally, by comparing the SPH results of slopes under different angles with and without vibration, this study obtains the variation rules of sliding material volume and influence range of soil slope under the seismic vibration. The greater the slope angle is, the greater the displacement of the slope will be with vibration, and the sliding material volume will present different trends under different displacement thresholds. Moreover, the horizontal displacement of the slope under the effect of earthquake increases non-linearly with the increase of slope incline angle.